2017
DOI: 10.2486/indhealth.2016-0127
|View full text |Cite
|
Sign up to set email alerts
|

Work, sleep, and cholesterol levels of U.S. long-haul truck drivers

Abstract: Long-haul truck drivers in the United States experience elevated cardiovascular health risks, possibly due to hypercholesterolemia. The current study has two objectives: 1) to generate a cholesterol profile for U.S. long-haul truck drivers; and 2) to determine the influence of work organization characteristics and sleep quality and duration on cholesterol levels of long-haul truck drivers. Survey and biometric data were collected from 262 long-haul truck drivers. Descriptive analyses were performed for demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
1
16
0
3
Order By: Relevance
“…107 This is supported by Lemke et al who found that 52.8% of truck drivers had an LDL level of >115 mg/dL. 61 …”
Section: Resultsmentioning
confidence: 84%
“…107 This is supported by Lemke et al who found that 52.8% of truck drivers had an LDL level of >115 mg/dL. 61 …”
Section: Resultsmentioning
confidence: 84%
“…The unique occupational milieu of the U.S. long-haul trucking industry, and especially its work organization and workplace characteristics, has been known to have detrimental impacts on the physical and psychological well-being of its drivers [23,76,77,78,79,80,81]. In turn, these physical and psychological consequences—including poor work-life balance—are believed to reduce the economic vitality and viability of the industry, with hypothesized impacts on numerous stakeholders, including drivers and their families, trucking companies, health care systems, and other roadway users [23,82,83,84,85,86,87].…”
Section: Discussionmentioning
confidence: 99%
“…These increasingly poor health trends may be related to multiple aspects of being a truck driver, including poor diet, lack of physical activity, stress, poor sleep, and lack of social support which have been reported in a handful of articles . One study reports relationships between near misses and measures of both safety climate and occupational stress .…”
Section: Discussionmentioning
confidence: 99%